"Command these elements to silence": Ecocriticism and The Tempest. Issue 3 (10th March 2020) - Gray, David
Abstract: As part of the response in the humanities to rising concerns of the human influence on the Earth system, ecocriticism – an interdisciplinary approach to the study of literature focused on ecological and environmental concerns – became a major trend in literary and cultural studies by the first decade of the twenty‐first century. This period also witnessed an increase in ecocritical studies of Shakespeare's works, which have continued to proliferate. It is timely therefore to consider those individual works that have interested ecocritics and featured in ecocritical studies. This article will provide just such a consideration of Shakespeare's final play, The Tempest (1611), providing a critical review of the play's ecocritical studies thus far, and drawing attention to central ideas and common themes in the process. Finally, the article offers its own ecocritical analysis of the play, based on historical accounts of a catastrophic tidal event that took place in south‐west England, in 1607.